MTCL1 plays an essential role in maintaining Purkinje neuron axon initial segment. (10th March 2017) - Satake, Tomoko; Yamashita, Kazunari; Hayashi, Kenji; Miyatake, Satoko; Tamura‐Nakano, Miwa; Doi, Hiroshi; Furuta, Yasuhide; Shioi, Go; Miura, Eriko; Takeo, Yukari H; Yoshida, Kunihiro; Yahikozawa, Hiroyuki; et al.
Abstract: The axon initial segment (AIS) is a specialized domain essential for neuronal function, the formation of which begins with localization of an ankyrin‐G (AnkG) scaffold. However, the mechanism directing and maintaining AnkG localization is largely unknown. In this study, we demonstrate that in vivo knockdown of microtubule cross‐linking factor 1 (MTCL1) in cerebellar Purkinje cells causes loss of axonal polarity coupled with AnkG mislocalization. MTCL1 lacking MT‐stabilizing activity failed to restore these defects, and stable MT bundles spanning the AIS were disorganized in knockdown cells. Interestingly, during early postnatal development, colocalization of MTCL1 with these stable MT bundles was observed prominently in the axon hillock and proximal axon. These results indicate that MTCL1‐mediated formation of stable MT bundles is crucial for maintenance of AnkG localization. We also demonstrate that Mtcl1 gene disruption results in abnormal motor coordination with Purkinje cell degeneration, and provide evidence suggesting possible involvement of MTCL1 dysfunction in the pathogenesis of spinocerebellar ataxia. Synopsis: Microtubule‐stabilizing protein, MTCL1, is required for maintaining ankyrin‐G localization to the AIS region of Purkinje cells. Analysis of mutant mice shows the importance of MTCL1 for Purkinje cell maintenance and cerebellar function. MTCL1 is required for maintaining ankyrin‐G localization to the AIS region of Purkinje cells. MTCL1 is required for formation of stable microtubule bundles at the AIS region. Microtubule‐stabilizing ability of MTCL1 is essential for the maintenance of ankyrin‐G localization. Mtcl1 mutant mice show motor coordination defects with Purkinje cell degeneration. Abstract : Loss of MTCL1‐dependent microtubule stabilization affects localization of the ankyrin‐G scaffold, causing Purkinje cell degeneration and abnormal motor coordination.